Influence of Absorptive Capacity and Creativity on Worker Performance with Social Media as Moderation - Farida Farida; Shinta Anisah Mahdiyani; Justine Tanuwijaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to examine The Effect of Absorptive Capacity and Creativity on Job Performance: The Moderating Role of Social Media Usage. The primary data collection method used is the questionnaire method the data were analyzed using Covariance-Based Structural Equation Modeling (SEM). The results of this study to show that absorptive capacity and creativity have a positive impact on job performance. The result also to show that social media usage has strengthened on the effect of absorptive capacity on job performance. In the contrary, the social media has no strength on the effect of creativity on job performance.